Assessment of Veterinary Extension Services Rendered to Poultry Farmers by the Agricultural Development Project, Kwara State, Nigeria - B. M, Matanmi; K. F. , Omotesho; K. S, Obaniyi; R. S, Adisa; J. D, Ogunsola (Asian Journal of Agriculture and Rural Development, 2012)
The study assessed the veterinary extension services rendered by the Kwara State Agricultural Development Project (KWADP) to poultry farmers in Kwara State, Nigeria. A two stage sampling procedure produced the sample size of 110 from five villages in the study area. A well structured interview schedule was administered to the respondents to produce data which was analyzed using both descriptive and inferential statistical tools. The study revealed that majority of the poultry farmers in the study area were male (73.3%), aged between 31 and 50 (70.9%) and had over 10 years experience in poultry farming (74.5%). Only 17.3% of the farmers had secondary school education. Almost all the respondents (97.35%) were aware of the veterinary services of the (KWADP). The frequency of extension contact was monthly for 59.1% of the respondents. The t-test at 1% level of significance revealed significant differences in the means of meat yield and egg yield before and after extension contact. The study concluded that though there was strong level of awareness of the veterinary services of the KWADP and there was evidence of positive impact of the extension contact on productivity, the extension service was not meeting the needs of the farmers in some aspects of poultry production such as facilitating credit facilities for expansion. The study recommended that the frequency of extension contact be improved upon. Lastly, the study suggested that farmers should be encouraged to form or join cooperative societies to brighten their chances of securing rural credit.